A simple PCR-based procedure for plaque diagnosis - Leal, Nilma Cintra; Abath, Frederico Guilherme Coutinho; Alves, Luis Carlos; Almeida, Alzira Maria Paiva de (Revista do Instituto de Medicina Tropical de São Paulo, 1996)
Supernatant of boiled spleen saline-suspensions of Yersinia pestis experimentally infected animals were used as template for PCR amplification without DNA extraction. PCR sensitivity was enhanced by a second round of amplification (Nested). No amplification was observed from non-infected animals.